Pengaruh Kualitas Produk Dan Harga Terhadap Keputusan Pembelian Skincare Skintific: Studi Pada Brand Skincare Skintific - Insania Alfi Mesita; Agus Wahyudi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research is a survey of skincare purchases. The purpose of this research is to find out how influential quality and price are on purchases. This research was analyzed using quantitative descriptive methods. Data from the Indonesian Beauty Industry Association shows that demand for skincare products continues to increase every year. Skintific's popularity continues to increase due to its focus on product quality. Prices and promotional activities also play an important role in helping consumers make better purchasing decisions. Skintific, as an international skin care brand, offers quality products without harmful ingredients that can cause irritation. With continuous innovation and use of natural ingredients, Skintific has succeeded in becoming a favorite skincare brand in Indonesia in a short time.